Ethnomathematics Exploration in The Joglo House of Banyumas - Setyaningrum, Agustina; Untarti, Reni (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2024)
Indonesia is known as a country with cultural diversity, one of which is the traditional house, a symbol of each tribe and region. In its implementation, the Joglo house is only used as a residence and a place to protect against exposure to sunlight. Still, after exploring it in more depth, the structure of the traditional house can be used as learning material in the field of education. One field of education that can study culture through the structure of conventional house buildings is mathematics. Learning mathematics that includes culture can help students improve their understanding of abstract mathematics. However, not many mathematics lessons incorporate culture into the material. So, this research aims to explore Banyumas Joglo houses regarding geometric concepts. The type of research used is qualitative research with an ethnographic approach. Data collection methods include observation, documentation and interviews. The data analysis consists of data reduction, data presentation, and conclusion. This research shows that the Banyumas Joglo traditional house is an example of a conventional house rich in ethnomathematics, where elements of traditional culture contain mathematical knowledge in the form of geometric concepts.